Evaluating the Relationship Between Measures of Diastolic Function and Exercise Capacity in Young and Healthy Adults: A Retrospective Analysis - LaGalbo, Serafino; Swearingen, Sean (Cardiology and Cardiovascular Medicine, 2025)
Background: Diastolic function during exercise is typically assessed via relationships between the early mitral inflow velocity (E) and early mitral annular tissue wave velocities (e’). Data involving patients over 50 years old suggests an increase in E/e’ with exercise indicates diastolic dysfunction. Limited data in young and healthy patients however suggests increases in E/e’ may actually be indicative of increased exercise capacity within this patient population, rather than diastolic dysfunction. Objectives: To determine correlation between changes in E/e’ and exercise capacity in a population of young and healthy adults. Methods: This retrospective study included 19 (12 men, 7 women) patients between the ages of 18-40 years that did not have a diagnosis of any cardiac or pulmonary disease who underwent exercise stress echocardiography. The primary outcome was the relationship between change in E/e’ and maximum METs achieved during testing. Secondary outcomes included sex-specific relationships between changes in E/e’ and overall performance on exercise stress testing. Results: Statistical analysis showed that increases in E/e’ values correlated with improved stress test performance (r = 0.65). The secondary outcome of sex-related changes in E/e’ from pre- to post-stress was significant in that the E/e’ in males increased by an average of 0.59 (SD 0.69) while female E/e’ had a non-statistically significant decrease with a mean change of -0.02 (SD 1.15). Overall, there was no significant change in E/e’ when comparing pre-and post-stress imaging. Conclusions: The study observed that while there was no significant change in E/e’ from pre- to post-stress, an overall increase in E/e’ value was positively correlated with maximum METs achieved during exercise stress testing, particularly in males.